TPACK-Integrated Zoology Vertebrate Booklet: Expert Validation of a Print Media Innovation Supporting Digital Learning - Fauziah, Nurul; Ade Rahma Yulis, Putri; Erfina; Hasanah Fitri, Rhada (Program Studi Pendidikan Biologi FKIP Universitas Pakuan, 2025)
The development of technology in the field of education requires innovation in the development of learning media that are not only print-based but also able to integrate pedagogical and technological aspects. However, many printed learning media are less than optimal in supporting digital learning. Therefore, this study aims to describe the validity value of the TPACK integrated vertebrate zoology booklet as an innovative learning media that supports the integration of technology in biology education. This type of research uses the Plomp development model which consists of three stages, namely preliminary research, prototype making, and assessment. The preliminary research stage has been carried out in previous studies, and in this follow-up study only the prototype making stage was carried out. The assessment stage will be carried out in the next survey. Validation was carried out by three expert validators, namely media experts, material experts, and learning experts. The validation results from media experts, material experts, and learning experts for this learning media are included in the valid and feasible category. In conclusion, the TPACK integrated vertebrate zoology booklet is feasible to use in learning. It is recommended to conduct further research to test the effectiveness and practicality of this TPACK integrated vertebrate zoology booklet in improving various competencies in students.